Study of Battery Charging Methods for Solar Renewable Storage Energy System - ROSDIN, MUHAMMAD FAKRUL FIRDAUS; Mustafa, Farahiya (Progress in Engineering Application and Technology, 2021)
In this paper, a simple battery charge controller using mostly discrete components is proposed and designed to protect the battery from overcharging and deep cycle discharges. The design consists of three stages which include current booster, battery charge controller and battery level indicator. The current produce by solar panel go through the current booster in order to maximize the value. The current booster is capable to control the current to make sure it get the maximum value current. LM317 voltage regulator are used to keep the voltage constant. The battery charger control are used to control the charging of the battery. This circuit are used the Integrated Circuit LM358 to control the charging process. The battery level indicator are used to indicate the battery if the battery is fully charged. This circuit are used operational amplifier and light-emitting diode (LED) to indicate the battery. The voltages are measured in the three stages of the circuit. The voltages are measured according to the time to detect the value through the circuit. The output voltages at 12 pm are measured to be 0.18 V, 0.27 V and 0.22 V for current booster, battery charger controller and battery level indicator, respectively. Normally, the higher the heat of the sunlight, the higher output voltage will be produced. The battery take about 5 hours to reach a full charge from 7.00 V to 12.34 V. This study is using locally sourced and available components that has developed a low cost, reliable and practical solar charge controller.